A novel strategy for the protective effect of ginsenoside Rg1 against ovarian reserve decline by the PINK1 pathway - Pengdi Yang; Meiling Fan; Ying Chen; Dan Yang; Lu Zhai; Baoyu Fu; Lili Zhang; Yanping Wang; Rui Ma; Liwei Sun (Pharmaceutical Biology)
Context The decline in ovarian reserve is a major concern in female reproductive health, often associated with oxidative stress and mitochondrial dysfunction. Although ginsenoside Rg1 is known to modulate mitophagy, its effectiveness in mitigating ovarian reserve decline remains unclear.Objective To investigate the role of ginsenoside Rg1 in promoting mitophagy to preserve ovarian reserve.Materials and methods Ovarian reserve function, reproductive capacity, oxidative stress levels, and mitochondrial function were compared between ginsenoside Rg1-treated and untreated naturally aged female Drosophila using behavioral, histological, and molecular biological techniques. The protective effects of ginsenoside Rg1 were analyzed in a Drosophila model of oxidative damage induced by tert-butyl hydroperoxide. Protein expression levels in the PINK1/Parkin pathway were assessed, and molecular docking and PINK1 mutant analyses were conducted to identify potential targets.Results Ginsenoside Rg1 significantly mitigated ovarian reserve decline, enhancing offspring quantity and quality, increasing the levels of ecdysteroids, preventing ovarian atrophy, and elevating germline stem cell numbers in aged Drosophila. Ginsenoside Rg1 improved superoxide dismutase, catalase activity, and gene expression while reducing reactive oxygen species levels. Ginsenoside Rg1 activated the mitophagy pathway by upregulating PINK1, Parkin, and Atg8a and downregulating Ref(2)P. Knockdown of PINK1 in the ovary by RNAi attenuated the protective effects of ginsenoside Rg1. Molecular docking analysis revealed that the ginsenoside Rg1 could bind to the active site of the PINK1 kinase domain.Discussion and conclusions Ginsenoside Rg1 targets PINK1 to regulate mitophagy, preserving ovarian reserve. These findings suggest the potential of ginsenoside Rg1 as a therapeutic strategy to prevent ovarian reserve decline.